Prevalence and associated factors of chronic venous insufficiency among seafood processing workers in Hai Phong, Vietnam - Tran Thi Quynh, Chi; Nguyen Van, Tam; Nguyen Hoang Viet, Duc; Le Thi, Van; Do Thi, Hai (International Journal of Occupational Safety and Health, 2024)
Introduction: Chronic venous insufficiency (CVI) is a condition that the function of venous system is impaired due to insufficiency of venous valves. The prolonged periods of standing or sitting is considered the most crucial risk factor of CVI. This study aims to determine the prevalence and associated factors of CVI among seafood processing workers. Methods: A cross-sectional study was conducted through clinical examination and face-to-face interviews with 1160 seafood processing workers in Hai Phong from March to November in 2023 to assess the prevalence and associated factors to CVI. Results: The prevalence of CVI was 51.9%; the prevalent symptom was restless legs (54.0%); nocturnal cramps (49.3%); tight feeling in calves (43.2%); pins and needles (36.4%); edema lower legs (28.6%). Of all participants 4.1% were C0, 82.9% were C1, 11.0% were C2 and 2.0% were C3. Some factors associated with CVI: female (OR = 2.51, p=0.002); advanced age; prolonged periods of standing or sitting (OR = 2.08, p=0.001); overweight and obesity (OR =1.82, p=0.037); Abdominal obesity (OR =2.11, p=0.025); diabetes (OR = 1.95, p=0.045); hypertension (OR =2.59, p=0.004); gave birth to 2 and 3 children (OR = 1.78 and 2.35, p=0.002); working time over 8 hours per day (OR =3.87, p<0.001). Conclusion: CVI is a disease with high incidence in seafood processing workers. On average, 1 of 2 workers have varicose veins. To prevent CVI, it is crucial to recommend workers exercise between shifts or breaks, have regular health check-ups to detect signs and symptoms of CVI.